Evaluation of implant site preparation with piezosurgery versus conventional drills in terms of operation time, implant stability and bone density (randomized controlled clinical trial- split mouth design) - Hani Arakji; Essam Osman; Nayer Aboelsaad; Mohamed Shokry (BMC, 2022)
Abstract Background The preparation of the implant bed has a major influence on the success rate and long-term survival of dental implants. Piezoelectric devices and special implant drilling inserts are now emerging to replace conventional drills showing improved bone response and healing around implants. The purpose of this study is to compare the piezoelectric inserts versus the traditional drills for implant site preparation. Methods Twelve male patients who received a total of twenty-four dental implants have been selected to participate in this split-mouth clinical trial. Each patient received two implants; one installed after piezosurgery assisted osteotomy, while the contralateral side received the implant with the original drilling protocol. The timing of surgery, implant stability, and bone density around the installed dental implants have been evaluated during a follow-up period extended to 4 months. Results a significant difference in terms of time of surgery (p < 0.005) and in implant stability at 4 months (p = 0.024) on the study side, while a non-statistical significance in terms of bone density was detected (p = 0.468). Conclusion The piezoelectric implant site drilling protocol seemed to be a reliable and repeatable technique. Despite the limited sample size and lengthier operative time, the piezoelectric inserts enhanced bone quality and implant stability. Clinical trial registration Current Controlled Trials (ClinicalTrials.gov) https://clinicaltrials.gov/ct2/show/NCT05512273 ; the date of registration: 23/08/2022. Retrospectively registered.